Large mass strandings of selected odontocete species: statistics, locations, and relation to earth processes - Hamilton, L.J. (J. Cetacean Res. Manage., 2023)
Larger mass strandings of open ocean odontocetes (toothed whales) of 10+ animals are examined with a compilation of 710 worldwide events. Six species form 96% of events (false killer, long-finned pilot, melon-headed, short-finned pilot, sperm and white whales), with beaked, killer, and pygmy killer whales forming 4%. Site type was determined for 630 events – three-quarters (76%) are in bays, 14% in shallow topographically complex areas (estuarine environments, straits, keys, reef and coastal lagoons), 8% on relatively unindented coasts, with ice entrapment (of killer whales) and miscellaneous categories being 2%. For the 76% of events in bays, sites with headland-bay character make up 42%, spit-bays 20% (even though there are only four of them), indented bays 9% and unspecified bay types 5%. Headland-bays and spit-bays become stranding sites through the properties endowed them by their mechanisms of formation and maintenance, but these mechanisms differ greatly for the two. Breakwaters, groyne series, tides, partial burial, and violent storms also appear as themes. Nearshore slopes are less than 1° for 94 of 105 sites having bathymetry information, with only two reaching or exceeding 3°. Some types of potential stranding sites can be identified by simple quantitative specifications for planform, sediment size, and seabed slope, although strandings will not necessarily occur there. There is an indication that larger strandings are globally correlated with areas of higher oceanic primary productivity near landmasses and oceanic islands, but quantitative studies are needed to clarify any such possible relationship. There is also an indication that larger strandings are associated with plate tectonics, with few events being seen on the steeper swell resistant active western margins of South America and South Island (New Zealand) in particular. In contrast several larger events are recorded for the relatively older passive margins of the south-eastern sides of these two landmasses, putatively because waves and swell have had time to construct stranding sites on them. Similarly, few larger events are seen for steeper shores adjacent to coastal highlands, such as those of South Africa and Brazil. These observations indicate previously unsuspected relations between the phenomenon of odontocete mass strandings and global scale earth and ocean processes, but they are essentially hypotheses in need of more quantitative examination.